‘Days of Frustration’: A Qualitative Study of Adolescents’ Thoughts and Experiences of Schooling after Early Dropout - Karl Ottar Ottosen; Charlotte Bjørnskov Goll; Rolf Wynn; Tore Sørlie (Behavioral Sciences, 2023)
School dropout increases the risk of unemployment, health problems, and disability benefits. Employing an ecological-developmental perspective, we analyzed the interviews of thirteen students from a peripheral Norwegian county, aiming to explore the possible influence of upbringing and schooling on dropout. The analysis revealed that dropout was associated with an unstable family situation, lack of structure in everyday life, unresolved complex learning difficulties, bullying, and a tough existence in a rented room. The participants conveyed a sense of defeat, frustration, and an absence of meaningful alternatives. However, two participants had actively chosen to discontinue their education; this was because they preferred work practice to allow them time to mature and re-orientate in relation to future educational and career choices. Their families and social networks contributed actively to the implementation of their future plans. The findings point to the importance of studying interventions that may prevent school dropout, and that address central factors in the process of school dropout, such as social support, academic achievement, and parental involvement.